2016
DOI: 10.14502/tekstilec2016.59.162-167
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field Effect on Charge-Discharge Characteristics of Textile-Based Energy Storage Devices: In Search of the Underlying Mechanism

Abstract: The work focused on studying the eff ect of charging voltage level and the absence of electrode between the measured electrodes on the charge storage profi le. The device was applied on a three layered of 5 x 5 cm laminated textile fabric with hydrophobic surface. Stainless steel fi lament yarns were used as electrodes. As electrolyte, seven layers of the electro-active polymer PEDOT:PSS dispersion was consecutively drop-coated and dried under the temperature of 90-100 °C. During the course of the experiments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…However, this was not the focus of this study, so we do not present any data or analysis regarding the distribution and molecular or electronic interaction of PEDOT:PSS in the cell area. As shown in Figure 2 , as a result of water repellent-pretreatment, PEDOT:PSS coating became concentrated within the cell area whereas in the devices reported previously [ 20 , 33 , 34 , 35 , 36 ], the polymer migrated out of the cell area. It demonstrated that the technique could be used to control the loading and distribution of PEDOT:PSS polymer dispersion during the coating process.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…However, this was not the focus of this study, so we do not present any data or analysis regarding the distribution and molecular or electronic interaction of PEDOT:PSS in the cell area. As shown in Figure 2 , as a result of water repellent-pretreatment, PEDOT:PSS coating became concentrated within the cell area whereas in the devices reported previously [ 20 , 33 , 34 , 35 , 36 ], the polymer migrated out of the cell area. It demonstrated that the technique could be used to control the loading and distribution of PEDOT:PSS polymer dispersion during the coating process.…”
Section: Resultsmentioning
confidence: 74%
“…However, in this study, a slight technical modification was done for the PEDOT:PSS coating method due to the hydrophobic surface properties of the fabric leading to having less amount of PEDOT:PSS polymer used for each device. With the perfect hydrophobicity on the fabric surface, there was no diffusion of the diluted polymer into the pores of the fabric as visually observed in the previous devices [ 33 , 34 , 35 ], and therefore, all polymer dispersion dropped into the cell surface could be completely distributed on the surface of the cell area. This way, instead of having seven drops, as described in the previous works, five drops were sufficient to cover the cell area.…”
Section: Methodsmentioning
confidence: 73%
See 1 more Smart Citation
“…Device preparation . Devices used for these experiments were slightly modified from the standard design we had developed in our earlier works [ 2 , 6 ]. Two threads of electrodes were utilized: one strand acted as counter and reference electrode, while the other was functioned as working electrode.…”
Section: Methodsmentioning
confidence: 99%
“…SEM (Scanning electron microscopy) imaging and energy dispersive X-ray (EDX) analysis on the device have shown the movement of silver ions through the PEDOT:PSS from the anode to cathode under the bias of high electric field. However, our works with stainless-steel electrode yarns have indicated that possible other mechanism may also have come into play suggesting intermediate situations or hybrid mechanisms between battery and capacitors [ 2 , 6 ]. A possible mechanism of charge storage could be that of charge separation within the structure of PEDOT:PSS.…”
Section: Introductionmentioning
confidence: 99%